Ethnobotanical study of Janachana community forest in Rautahat district, Nepal - Gautam, Santosh Kumar; Magar, Gyanu Thapa; Chhetri, Mukesh Kumar; Chaudhary, Sujan (Himalayan Journal of Science and Technology, 2022)
Community forest user groups (CFUGs) have been receiving different ecosystem services and facilities from the community forest, which are very crucial in their daily life activities. The present study is aimed at identifying the facilities and services received from the different plant species in the Janachana Community Forest, Rautahat district, Nepal. Altogether, 84 members of community forest groups participated in an interview using a semi-structured questionnaire. In total, 65 plants were identified in the study area for use as medicine, firewood, fodder, bedding, food, and other purposes. However, most plants were used as fodder for livestock. Altogether, fifty-eight plant species (89%) were used for multiple purposes (more than one use) and seven (11%) species were used for single purpose. Among the reported plant species, thirty species were used for medicinal purposes. Seeds and leaves were common parts of the plant used as medicine. Most of the plants were used to treat gastritis, cough, and blood clots, which seem to have high prevalence inthe study area. These results imply the various benefits taken by the CFUGs from the community forest in their daily life.